Clinical Supervision Among Family Physicians - Martina A. Torppa; Kristiina Toivola; Juho Ruskoaho; Kaisu H. Pitkälä (SAGE Publishing, 2013)
Background: Clinical supervision (CS) is not an established support system among physicians. Family physicians (FPs) have used Balint groups as a form of clinical supervision. In all, not much is known about the prevalence of physicians' attendance to or needs for CS. Objective: We studied what proportion of FPs compared with other physicians have attended or report they would need CS and whether having patients who request certain tests or medicines is associated with FPs' attendance to or need for CS. Design: A postal survey for all working-aged Finnish physicians was performed in 2008. Special questions concerning CS (eg, Balint) and patients' requests were included. Results: Response rate for the survey was 74% (N = 13 708). Special questions were responded by 10 559 physicians of whom 1252 were FPs. FPs had attended CS more often than other physicians (42% vs 29%, P < .001). Of FPs, 25% reported a need for CS with no availability of it. FPs experienced with or needing for CS were more often than other FPs females, had participated in continuing medical education, and reported that patients with requests have increased in recent years. Conclusion: Both experience of CS and a need for CS with no availability are common among Finnish FPs. Experiences of patients with requests may reflect a need for CS among FPs. Studies on the content, significance and effectiveness CS among FPs are needed.